(untitled) (Bangladesh Journal of Physics, 2026)
This study presents a detailed simulation of the neutron and photon flux distribution as well as their energy spectra within the PGAA system of the Moroccan TRIGA Mark II reactor. The simulation was carried out using the PHITS Monte Carlo code. Several configurations were analyzed, particularly the collimator, the sapphire filter, the closed shutter, and the open shutter. The simulation results show that the sapphire filter significantly attenuates gamma rays, thereby reducing contamination of the PGAA detector. The closed shutter configuration effectively blocks neutrons and photons, especially fast neutrons, while the open shutter configuration allows the complete passage of the neutron beam with well-collimated propagation, thus providing valuable information on the performance of the PGAA system. Bangladesh Journal of Physics, Vol. 32, Issue 2, pp. 1 – 12, December 2025